The Language of Paradox in the Ironic Poetry of Emily Dickinson - Cirakli, Mustafa Zeki (Journal of History Culture and Art Research, 2015)
The Language of Paradox in the Ironic Poetry of Emily Dickinson Abstract Emily Dickinson’s poetry is characterized by her emphasis on ironic use of discourse that amounts to her persistent manifestation of individuality against hypocrisy and vanity. She exerts her peculiar poetic language in a way that helps deplore as well as explore the paradoxical human condition. This paper argues that Dickinson produces a language of poetry, which, in Cleanth Brooks’ terms, provides the reader with the “language of paradox.” Dickinson’s ironic poetry exemplifies Brooks’ idea that ironic poetry is self-conscious and satiric in nature and is made up of a language of paradox. The study, therefore, aims to reveal how the language of paradox in Dickinson’s poetry yields to irony which is primarily associated with her salient assertiveness, isolation and strong individuality. Emily Dickinson’ın İronik Şiirlerinde Paradokslu Dil Öz Emily Dickinson’ın şiirlerini söylemin ironik kullanımı karakterize eder ve bu özellik onun şiirlerinin toplumdaki iki yüzlülük ve riyakârlığa karşı sürdürdüğü kararlı bireysel duruş ve isyanının dışavurumudur. Dickinson, kendine özgü şiirsel dili insanlık durumunun paradoksal niteliğini araştırmak için olduğu kadar eleştirmek için de etkili biçimde kullanmıştır. Dickinson’ın şiiri, Cleanth Brooks’un “paradokslu dil” olarak tanımladığı bir dil kullanır. Brooks, ironik şiirin öz-farkındalığı olan ve doğası gereği eleştirel tonu yüksek ve temelde paradokslu dilden oluşmuş olduğunu ileri sürer. Bu çalışma, Dickinson’ın ironik şiir dilinin Brooks’un bu kanısını doğruladığını ortaya koymaktadır. Dolayısıyla bu çalışma, Dickinson’un şiirlerindeki paradokslu dilin yazarın dikkat çekici sesi, kendini toplumdan soyutlaması ve toplum karşısındaki güçlü bireyselliğinin dışa vurumunu imleyen ironiyi incelemektedir.